An investigation into the role of childhood trauma and inflammatory profiles in depression. (September 2021) - Worrell, C.; Cattaneo, A.; Ferrari, C.; Turner, L.; Mariani, N.; Enache, D.; Hastings, C.; Lombardo, G.; McLaughlin, A.P.; Nettis, M.A.; Nikkheslat, N.; Zajkowska, Z.; et al.
Abstract : Background: Inflammatory pathways of depression are of interest, and the influence of childhood trauma proposed. Methods: 130 depressed cases and 40 controls were recruited in the BIOmarkers in DEPression study. Inflammatory markers were measured, and mRNA qPCR performed. Depression was measured by the Hamilton-Depression Rating Scale, and trauma by the Childhood Trauma Questionnaire. Results: T-tests in the whole sample highlighted those with childhood trauma (CT) (N=123) showed higher mean serum c-reactive protein (mg/L) (m=.9737, SE=.702) than those with no CT (N=47) (m=.7521, SE=.0830) (p=0.046). A one-way ANOVA identified associations between CT and 7 genes. The most significant associations were A2M (alpha-2-macroglobulin) (p=.005), FKBP5 (FK506 binding protein 51) (p=.025) and NR3C1 (glucocorticoid receptor) (p<.001). T-tests showed A2M was higher in CT+ group (m=.7950, SE=.0084) compared to CT- (m=.7427, SE=.0159), as for FKBP5, with CT+ (m=.7889, SE=.0081) and CT- (m=.7493, SE=.0098). CT+ (m=.6435, SE=.0064) showed a decrease in NR3C1 compared to CT- (m=.6900, SE=.0085). Conclusions: These findings suggest that presence of CT was associated with inflammatory gene expression in this sample. Further investigation is needed.